Optimization of adolescent and young adult mental health assessment and ideological-political intervention strategies based on biological analysis - Meng, Dawei (Molecular & Cellular Biomechanics, 2024)
The present work is a cross-sectional study seeking to improve the assessment of student mental health by including. It not only utilizes the standard rating scale but also incorporates cortisol levels and genetic factors. The study delves into the role of various factors. In terms of biological aspects, it focuses on the molecular mechanisms underlying cortisol and genetic markers, and details the methodologies for their measurements. Regarding sociopolitical factors, it analyzes the impacts of stigma, societal pressures, and academic policies on students’ mental wellbeing. Moreover, it emphasizes the intricate interactions between biological, psychological, and sociopolitical dimensions. The research adopts a quantitative research design complemented by qualitative research data collection and analysis tools. In the quantitative phase, 400 high school and university students are recruited. They fill in psychometric questionnaires such as the Beck Depression Inventory, State-Trait Anxiety Inventory, and Perceived Stress Scale, along with providing biological measures like cortisol levels Participants are matched by age, gender, and socio-economic status. As part of the qualitative analysis, 50 students are invited for focus group interviews to get their understanding of mental health issues, social norms, and the college rules and regulations. The data collection was done through stratified random sampling to ensure a comprehensive representation. The results indicate that high cortisol levels are positively related to depression and anxiety scores, which validates the significance of biological factors in mental disorders. Additionally, the quantitative findings highlight crucial sociopolitical factors like stigma and academic pressure that exacerbate mental health problems. To enhance the efficiency of mental health evaluation and treatment, a holistic approach considering biological, psychological, and Socio-political factors is essential. However, the study has limitations such as the lack of transferability of findings to other populations and the potential influence of self-report measures in psychometric results.